Hospitality English Vocabulary Mastery: A Qualitative Descriptive Study on Student Performance with Wordwall Games - Sabiku, Sri Ariyanti (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to evaluate English vocabulary mastery among tourism students in the hospitality sector. Seven key areas of vocabulary proficiency were assessed, encompassing basic hotel vocabulary, travel and tourism terminology, hotel systems and operations, hotel services and amenities, room types, marketing and promotion, and hotel department functions. A qualitative descriptive method was employed, involving 26 purposively sampled tourism students from Universitas Negeri Gorontalo during the even semester of the 2023-2024 academic year. Data were collected through direct observation and vocabulary tests, designed using four game-based activities on the Wordwall platform: wordsearch, anagram, gameshow quiz, and match-up. The findings reveal significant variation in vocabulary mastery across different topics. The "Travel and Tourism Terminology" topic achieved the highest average score at 89%, followed by "Hotel Services and Amenities" at 71%, "Basic Hotel Vocabulary" at 63%, "Hotel Department Functions" at 59%, "Room Types" at 54%, "Marketing and Promotion" at 48%, and "Hotel Systems and Operations" at 37%.  The “Wordsearch” and “Gameshow Quiz” games were found to be easier,“Match Up” presented a moderate to high level of difficulty, and “Anagram” was the most challenging, requiring quick and logical thinking. The study highlights the need for increased focus on topics with lower vocabulary proficiency to enhance student competence. It recommends the use of Wordwall as an effective instructional tool, but it should be integrated with supplementary teaching strategies to address the challenges in mastering specific vocabulary.